The effects of kaolin and calcined kaolin on the durability and mechanical properties of self-compacting mortars subjected to high temperatures - Karatas, Mehmet; Benli, Ahmet; Arslan, Furkan (Elsevier Sci Ltd, 2020)
This study implemented an experimental program to evaluate the effects of kaolin (K) and calcined kaolin (CK) replacing cement partially on the durability and mechanical characteristics of self-compacting mortars (SCMs) at high temperature up to 900 degrees C and at room conditions. The cement was partially replaced by kaolin and calcined kaolin at the substitution rates of 0%, 5, 10, 15 and 20% on weight basis. The assessments of strength properties were done by compressive strength and flexural strength test on 3, 28 and 90 day- water cured 40x40x160 mm beam specimens at ambient conditions and the mechanical performance at high temperature was evaluated on the 28 day-water cured specimens. 28 day-50x50x50 mm cube specimens cured in water were used to assess the transport properties. For assessment of rheological and fresh properties, the viscosity test, slump and V-funnel tests were performed. The results of the study show that increasing flowability of fresh mixtures was observed with inclusion rates of K and CK. It was found that the compressive strength of K20 reduced about 18.40% in comparison to control samples at 28 days of curing age. Results illustrated that 8.42% and 14.65% of the flexural strength decrease of K20 and CK20 aged 28 days was observed comparing control specimens respectively. The introduction of CK into SCMs mixes decreased the compressive strength about 31.94%, 25%, 22.51% and 24.68%, and 74.30%, 69.17%, 67.35% and 68.28% at the inclusion rates of 5,10,15 and 20 CK at 600 degrees C and 900 degrees C respectively. A slight enhancement in the compressive strength of K and CK incorporated SCMs mixes was reported with temperature and content increment. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Mechanical Properties; Elevated Temperature; Self-Compacting Mortars; Kaolin; Calcined Kaolin; Transport Properties